Non-covalent interactions in extended systems described by the effective fragment potential method: theory and application to nucleobase oligomers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Williams, Christopher F.; Herbert, John M.; Gordon, Mark S.; Schmidt, Michael W.; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2010)
The implementation of the effective fragment potential (EFP) method within the Q-CHEM electronic structure package is presented. The EFP method is used to study noncovalent π-π and hydrogen-bonding interactions in DNA strands. Since EFP is a computationally inexpensive alternative to high-level ab initio calculations, it is possible to go beyond the dimers of nucleic acid bases and to investigate the asymptotic behavior of different components of the total interaction energy. The calculations demonstrated that the dispersion energy is a leading component in π-stacked oligomers of all sizes. Exchange-repulsion energy also plays an important role. The contribution of polarization is small in these systems, whereas the magnitude of electrostatics varies. Pairwise fragment interactions (i.e., the sum of dimer binding energies) were found to be a good approximation for the oligomer energy.

Effect of solvation on the vertical ionization energy of thymine: from microhydration to bulk - Ghosh, Debashree; Isayev, Olexandr; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2011)
The effect of hydration on the vertical ionization energy (VIE) of thymine was characterized using equation-of-motion ionization potential coupled-cluster (EOM-IP-CCSD) and effective fragment potential (EFP) methods. We considered several microsolvated clusters as well as thymine solvated in bulk water. The VIE in bulk water was computed by averaging over solvent-solute configurations obtained from equilibrium molecular dynamics trajectories at 300 K. The effect of microsolvation was analyzed and contrasted against the combined effect of the first solvation shell in bulk water. Microsolvation reduces the ionization energy (IE) by about 0.1 eV per water molecule, while the first solvation shell increases the IE by 0.1 eV. The subsequent solvation lowers the IE, and the bulk value of the solvent-induced shift of thymine's VIE is approximately -0.9 eV. The combined effect of the first solvation shell was explained in terms of specific solute-solvent interactions, which were investigated using model structures. The convergence of LE to the bulk value requires the hydration sphere of approximately 13.5 angstrom radius. The performance of the EOM-IP-CCSD/EFP scheme was benchmarked against full EOM-IP-CCSD using microhydrated structures. The errors were found to be less than 0.01-0.02 eV. The relative importance of the polarization and higher multipole moments in EFP model was also investigated.

Effective fragment potential method in Q-CHEM: a guide for users and developers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Flick, Joanna; Kaliman, Ilya; Shao, Yihan; Gilbert, Andrew T. B.; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Computational Chemistry, 2013)
A detailed description of the implementation of the effective fragment potential (EFP) method in the Q-CHEM electronic structure package is presented. The Q-CHEM implementation interfaces EFP with standard quantum mechanical (QM) methods such as HartreeFock, density functional theory, perturbation theory, and coupled-cluster methods, as well as with methods for electronically excited and open-shell species, for example, configuration interaction, time-dependent density functional theory, and equation-of-motion coupled-cluster models. In addition to the QM/EFP functionality, a fragment-only feature is also available (when the system is described by effective fragments only). To aid further developments of the EFP methodology, a detailed description of the C++ classes and EFP module's workflow is presented. The EFP input structure and EFP job options are described. To assist setting up and performing EFP calculations, a collection of Perl service scripts is provided. The precomputed EFP parameters for standard fragments such as common solvents are stored in Q-CHEM's auxiliary library; they can be easily invoked, similar to specifying standard basis sets. The instructions for generating user-defined EFP parameters are given. Fragments positions can be specified by their center of mass coordinates and Euler angles. The interface with the IQMOL and WEBMO software is also described. (c) 2013 Wiley Periodicals, Inc.
Keywords: effective fragment potential; EFP library; hybrid QM; IQMOL; MM; modular code; nonempirical force field; Q-CHEM; WEBMO

Extension of the effective fragment potential method to macromolecules - Gurunathan, Pradeep Kumar; Acharya, Atanu; Ghosh, Debashree; Kosenkov, Dmytro; Kaliman, Ilya; Shao, Yihan; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Physical Chemistry B, 2016)
The effective fragment potential (EFP) approach, which can be described as a nonempirical polarizable force field, affords an accurate first-principles treatment of noncovalent interactions in extended systems. EFP can also describe the effect of the environment on the electronic properties (e.g., electronic excitation energies and ionization and electron-attachment energies) of a subsystem via the QM/EFP (quantum mechanics/EFP) polarizable embedding scheme. The original formulation of the method assumes that the system can be separated, without breaking covalent bonds, into closed-shell fragments, such as solvent and solute molecules. Here, we present an extension of the EFP method to macromolecules (mEFP). Several schemes for breaking a large molecule into small fragments described by EFP are presented and benchmarked. We focus on the electronic properties of molecules embedded into a protein environment and consider ionization, electron-attachment, and excitation energies (single-point calculations only). The model systems include chromophores of green and red fluorescent proteins surrounded by several nearby amino acid residues and phenolate bound to the T4 lysozyme. All mEFP schemes show robust performance and accurately reproduce the reference full QM calculations. For further applications of mEFP, we recommend either the scheme in which the peptide is cut along the C-alpha-C bond, giving rise to one fragment per amino acid, or the scheme with two cuts per amino acid, along the C-alpha-C and C-alpha-N bonds. While using these fragmentation schemes, the errors in solvatochromic shifts in electronic energy differences (excitation, ionization, electron detachment, or electron-attachment) do not exceed 0.1 eV. The largest error of QM/mEFP against QM/EFP (no fragmentation of the EFP part) is 0.06 eV (in most cases, the errors are 0.01-0.02 eV). The errors in the QM/molecular mechanics calculations with standard point charges can be as large as 0.3 eV.